The situation of transplantation of hematopoietic trunk cells in the state of Pará, Amazônia in the period from January 2010 to December 2015 - Tobelem, Felipe Lima Alcolumbre; Zemero, Maria Isabel Muniz; Brito Junior, Lacy Cardoso de; Beltrão, Ana Cristina Simões; Amazonas, Kennie Kelly dos Santos (Brazilian Journal of Transplantation, 2018)
Introduction: Even with the expansion of units and beds for hematopoietic stem cell transplants (HSCT), and HLA laboratory, throughout Brazil, we are still far short in relation to the existing demand. Purpose: To understand the flow and characterize patients from the State of Pará registered in the REREME waiting for a HSCT from January 2010 to December 2015. Material and Methods: A descriptive, retrospective study on the flow gender, age and underlying disease (oncohematologic) of patients above 18 years of age, enrolled in the REREME by the State of Pará, waiting, or who have already performed HSCT from data obtained from REREME, CNCDO / SESPA and Immunogenetics Management (GERIM) of the HEMOPA Foundation. Results: It was observed that 30.1% patients were enrolled in REREME (82/272); 69.8% (190/272) performed research for HLA, but were not enrolled in REREME; 54.9% (45/82) presented acute lymphoid leukemia or acute myeloid leukemia or non-Hodgkin’s lymphoma; 45.12% (37/82) were between 18-30 years old; 48.78% (40/82) presented positive cytomegalovirus sorology; 52.43% (43/82) were men; and 2.43% (2/82) of the HSCT were performed outside the State of Pará. Conclusion: Data obtained show that this is not possible just using control systems of the Ministry of Health and REREME, the safe planning of public policies to support the need for HSCT for patients from the state of Pará.